2006
DOI: 10.1158/1535-7163.mct-05-0495
|View full text |Cite
|
Sign up to set email alerts
|

β-Escin inhibits colonic aberrant crypt foci formation in rats and regulates the cell cycle growth by inducing p21waf1/cip1 in colon cancer cells

Abstract: Extracts of Aesculus hippocastanum (horse chestnut) seed have been used in the treatment of chronic venous insufficiency, edema, and hemorrhoids. Most of the beneficial effects of horse chestnut are attributed to its principal component B-escin or aescin. Recent studies suggest that B-escin may possess anti-inflammatory, antihyaluronidase, and anti-histamine properties. We have evaluated the chemopreventive efficacy of dietary B-escin on azoxymethane-induced colonic aberrant crypt foci (ACF). In addition, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 44 publications
6
60
0
Order By: Relevance
“…p21 Cip1/Waf1 has been shown to regulate cell cycle progression in both G1 and G2 phases through p53-dependent or p53-independent pathways (Niculescu, Chen et al 1998). Consistent with the findings of previous research (Patlolla, Raju et al 2006), neither DU-145 nor PC-3 cell lines expressed functional p53 (Fan, Kumaravel et al 2004) in the present study , suggesting that p53 may not play an essential role in escin-induced apoptosis or conventional chemotherapeutic agents is mediated by p53 (Brown and Wouters 1999), the p53-independent activation of p21 WAF1/CIP1 triggered by escin treatment can represent an alternative therapeutic approach for prostate cancer patients who fail to respond to conventional agents targeting p53 . inactive.…”
Section: Escin Induces Cell Cycle Arrest At G2/m Phase and Modulates supporting
confidence: 89%
See 2 more Smart Citations
“…p21 Cip1/Waf1 has been shown to regulate cell cycle progression in both G1 and G2 phases through p53-dependent or p53-independent pathways (Niculescu, Chen et al 1998). Consistent with the findings of previous research (Patlolla, Raju et al 2006), neither DU-145 nor PC-3 cell lines expressed functional p53 (Fan, Kumaravel et al 2004) in the present study , suggesting that p53 may not play an essential role in escin-induced apoptosis or conventional chemotherapeutic agents is mediated by p53 (Brown and Wouters 1999), the p53-independent activation of p21 WAF1/CIP1 triggered by escin treatment can represent an alternative therapeutic approach for prostate cancer patients who fail to respond to conventional agents targeting p53 . inactive.…”
Section: Escin Induces Cell Cycle Arrest At G2/m Phase and Modulates supporting
confidence: 89%
“…The retinoblastoma (Rb) tumor suppressor gene product phosphorylated-Rb (pRb) serves as a downstream mediator of p21 (Schafer 1998) and plays a crucial role in cell cycle control. Patlolla et al (Patlolla, Raju et al 2006) report that pRb is inhibited by escin. Qiu et al (Qiu, Schönthal et al 1998) demonstrate that the loss of functional pRb leads to G2/M arrest following p21 induction in the human osteosarcoma cell line Saos-2 .…”
Section: Escin Induces Cell Cycle Arrest At G2/m Phase and Modulates mentioning
confidence: 98%
See 1 more Smart Citation
“…The pentacyclic triterpenoid b-escin was recently found to exhibit significant antitumor effects in human hepatocellular carcinoma both in vitro and in vivo (Zhou et al 2009). In addition, this effect of b-escin has also been reported to suppress colonic aberrant crypt foci formation in rats and to inhibit growth of colon cancer cells (Patlolla et al 2006). On the other hand, diosgenin and butein were shown to inhibit P-STAT3 through the induction of phosphatases.…”
Section: Hepatocellular Carcinomamentioning
confidence: 96%
“…b-Escin has been used widely to treat chronic venous insufficiency (4), hemorrhoids, and postoperative edema resulting from surgery (5). Studies from our laboratory showed that b-escin inhibits the growth of colon cancer cells and inhibits chemically induced colon carcinogenesis in rats (6). In recent years, several studies have shown that b-escin possesses anticancer activity by inhibiting growth and inducing apoptosis in various human cancer cell lines derived from lung (7), pancreatic (8), and liver (9) cancers and in leukemia and multiple myeloma (10).…”
Section: Introductionmentioning
confidence: 99%